2000
DOI: 10.1021/ie000437f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Domain and Similarity Models for Characterizing Moisture Sorption Equilibria of Paper

Abstract: Everett's domain and Mualem's capillary-radii similarity models of hysteresis were used to characterize the moisture sorption equilibria of a bleached kraft paperboard of mean basis weight 230 g/m2. The models predicted the experimental equilibrium moisture content (EMC) of the paperboard for the case of desorption scanning (similarity model only), adsorption scanning, spiral, and loop trajectories inside the main sorption hysteretic loop with good precision. Over an RH range of 15−90%, the root-mean-square de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Chatterjee [35,36] for bleached Kraft paperboard, C=56.0, K=0.75 and monolayer moisture content of 5.10%. The GAB parameter C is related to the magnitude of the enthalpy difference in the upper layers and in the monolayer, while the constant K is related to measurement of the difference of enthalpy in the sorbate's pure liquid state and in the upper layers (layers above the monolayer).…”
Section: Nfc Filmmentioning
confidence: 99%
“…Chatterjee [35,36] for bleached Kraft paperboard, C=56.0, K=0.75 and monolayer moisture content of 5.10%. The GAB parameter C is related to the magnitude of the enthalpy difference in the upper layers and in the monolayer, while the constant K is related to measurement of the difference of enthalpy in the sorbate's pure liquid state and in the upper layers (layers above the monolayer).…”
Section: Nfc Filmmentioning
confidence: 99%
“…Under high humidity conditions, paper has been known to show lower elastic moduli, yield stresses, and tensile strengths (TSs; Bandyopadhyay and others 2002). Though the moisture content of paper materials affect the mechanical properties of paper‐based packaging materials, the moisture content is directly related to the humidity of external environment (Eagleton and Marcondes 1994; Marcondes 1996; Chatterjee 2001; Parker and others 2006). It is therefore important to understand how the moisture content varies under different environmental conditions such as environment's relative humidity (RH) and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Further research has shown that the problem is much more difficult, and that the summary curves suggested here are simplifications of the problem. The equilibrium moisture content in paper has been shown to form a hysteresis loop [113][114][115]. Detailed studies have been conducted to model heat and mass transport in paper [116,117].…”
Section: Air and Paper Moisture Equilibriumsmentioning
confidence: 99%